Integrating Traditional Applied Arts into Contemporary Art Education: Pedagogical Approaches - Toshmuhammedova Iroda Alibek qizi, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the integration of traditional applied arts into contemporary art education and its pedagogical significance. Incorporating cultural heritage into the curriculum enhances students’ aesthetic awareness, creative thinking, and socio-cultural competence. The study analyzes methods for blending traditional techniques with modern art practices and provides practical recommendations for educators to effectively implement this integration.